The powdery mildew resistance protein RPW8.2 is carried on VAMP721/722 vesicles to the extrahaustorial membrane of haustorial complexes. (23rd July 2014) - Kim, Hyeran; O'Connell, Richard; Maekawa‐Yoshikawa, Makoto; Uemura, Tomohiro; Neumann, Ulla; Schulze‐Lefert, Paul
Summary Plants employ multiple cell‐autonomous defense mechanisms to impede pathogenesis of microbial intruders. Previously we identified an exocytosis defense mechanism in Arabidopsis against pathogenic powdery mildew fungi. This pre‐invasive defense mechanism depends on the formation of ternary protein complexes consisting of the plasma membrane‐localized PEN1 syntaxin, the adaptor protein SNAP33 and closely sequence‐related vesicle‐resident VAMP721 or VAMP722 proteins. The Arabidopsis thaliana resistance to powdery mildew 8.2 protein (RPW8.2) confers disease resistance against powdery mildews upon fungal entry into host cells and is specifically targeted to the extrahaustorial membrane (EHM), which envelops the haustorial complex of the fungus. However, the secretory machinery involved in trafficking RPW8.2 to the EHM is unknown. Here we report that RPW8.2 is transiently located on VAMP721/722 vesicles, and later incorporated into the EHM of mature haustoria. Resistance activity of RPW8.2 against the powdery mildew Golovinomyces orontii is greatly diminished in the absence of VAMP721 but only slightly so in the absence of VAMP722. Consistent with this result, trafficking of RPW8.2 to the EHM is delayed in the absence of VAMP721. These findings implicate VAMP721/722 vesicles as key components of the secretory machinery for carrying RPW8.2 to the plant–fungal interface. Quantitative fluorescence recovery after photobleaching suggests that vesicle‐mediated trafficking of RPW8.2–yellow fluorescent protein (YFP) to the EHM occurs transiently during early haustorial development and that lateral diffusion of RPW8.2–YFP within the EHM exceeds vesicle‐mediated replenishment of RPW8.2–YFP in mature haustoria. Our findings imply the engagement of VAMP721/722 in a bifurcated trafficking pathway for pre‐invasive defense at the cell periphery and post‐invasive defense at the EHM.